The road to a free market- law, legislation and the entrepreneurship - Munteanu, Ligia (Studies and Scientific Researches. Economics Edition, 2010)
The development of a country depends on the legal system of that country. Romanian aconomy haw knoweded, as many states, different ideologies and govemental methods, the segnificant difference< beetween then being the degree of state interventionism in the economy. To obtain a free market, we need a proper legal system, a special guvernmental attitude and a good implementation of the state of law principles and democracy. As we feel the need of change, the state tries to come with new programs and perspectives. The result is a legislative inflation, that scares any antreprenorial initiative. But there is another way of forming new institutions or changing them, more appropriate to the market. This is the way based on practical experience, tradition and responsability.